Trauma unit admissions at the Ugandan National Referral Hospital: a descriptive study - Luggya, Tonny Stone; Ngabirano, Annet Alenyo; Sarah, Richardson; Mabweijano, Jackie; Osire, John; Achieng, Lilian; Nabulime, Josephine; Bangirana, Alex (African Health Sciences, 2022)
Injuries are a neglected epidemic globally accounting for 9% global deaths; 1.7 times that of HIV, TB and malaria combined. Trauma remains overlooked with key research and data focusing on infectious diseases yet Uganda has one of the highest rates of traumatic injury. We described demographics of patients admitted to Mulago Hospital’s Shock Trauma Unit within the Emergency Department. This was a retrospective record review Trauma Unit admissions from July 2012 to December 2015. Information collected included: age, sex, time of admission, indication for admission and mechanism of trauma. 834 patient records were reviewed. The predominant age group was 18-35 with majority of patients being male. 54% of patients presented during daytime with 46% admitted in the evening hours or overnight. Mechanism of injury was documented in 484 cases. The most common mechanism was Road Traffic Accident (67.4%), followed by assault (12.8%) and mob violence (5.6%). The most common indication for admission was traumatic brain injury (84.5%), followed by haemodynamic instability (20.0%) and blunt chest injury (6.1%).There’s a significant burden of high-acuity injury particularly among males with RTAs as the leading cause of admission associated with Traumatic Brain Injury as main admission indication.
Keywords: Emergency care; Trauma; Uganda; Traumatic Brain Injuries; Accidents, Injury.